Employing the Infographic on the Syrian TV channel Pages on Facebook –Analytical Study- (Damascus University Journal of arts and humanities sciences, 2024)
The aim of this research is to identify the size of the use of the infographic on the Syrian TV channel pages on Facebook, by applying it on the channel pages: "Syrian News", "Al-Souria," and "Syrian Education", where the researcher relied on the infographic as a main unit in analyzing these channels using the content and form analysis tool according to the comprehensive inventory method during the period from 4/2/2022 to 5/8/2022, which included /98/ infographics and /31/ analysis categories.The results of the study showed that the “Syrian Education” channel ranked first in the amount of using the infographic on its Facebook page, and the “Al-Souria” channel came in second place, then the “Syrian News” channel page came in the third place. The results of the study also revealed that educationaltopics came at the forefront of the topics covered by the infographic, and that the static infographic ranked first, with a complete absence of interactive infographics on the pages of the three channels of the study sample.
Keywords: Infographic; Facebook; TV